Designing better performance measurement systems in universities using the business model canvas - Franco-Santos, Monica (POMS, 2016)
This paper starts by critically reviewing the way in which universities design their measures of performance. We argue that the “one size fits all” performance measurement approach adopted by so many universities is not appropriate when departments have very different operating models. The paper proposes using “business model design” to enable university departments and centres to design and develop their own “sustainability model”, which in turn may help them develop more appropriate performance measurement systems. Using the lens of business model design may help universities to recognise their diversity and allow them to use performance measures more strategically
Keywords: Performance measurement; Business model canvas; Universities